Getting Youngsters Hooked on News: The effects of narrative news on information processing and appreciation in different age groups. (26th October 2018) - Kleemans, Mariska; Schaap, Gabi; Suijkerbuijk, Mitchel
Abstract : Narrative news is often propagated as a means to inform and attract younger generations of news consumers. To test this, the current study assessed the effects of narrative structure versus inverted pyramid structure on information processing and news appreciation for Millennials, compared to Generation X, and Baby Boomers/Silent Generation. Participants were randomly exposed to either four online news articles written in a narrative structure or an inverted pyramid structure. Results show that people are better informed by narrative news. However, appreciation is lower for narrative news compared to the inverted pyramid. Moreover, the younger participants express lower appreciation, regardless of story structure. The results suggest that although the narrative structure is best at informing all audiences, it is not necessarily a viable strategy to attract younger news audiences.